Deconstructing the glass ceiling: gender equality in the Australian property profession. Issue 1 (15th February 2016) - Warren, Clive M J; Antoniades, Hera
Abstract : Purpose: – The purpose of this paper is to export the role of professional bodies within the property industry in Australia in bringing about gender equality. In particular the policy objectives of the various professional bodies is analysed and contrasted with the level of genres equality demonstrated within the governance structures of the organisations at national and regional level. Design/methodology/approach: – The paper analyses the annual reports of the leading property professional bodies in Australia to identify any gender equity policy objectives and to identify the balance between male and female representation in the governing boards of the associations. Findings: – The research shows that while a few organisations have made some statements regarding the need for change to a more inclusive property industry these objectives are not reflected within the governance structure of the organisations. It is therefore evident that significant attitudinal and structural change will be required to bring about equality within the property industry. Research limitations/implications: – The research is limited to the Australian property and construction industry and the relevant boards at national and state level. Practical implications: – The paper highlights the need to address gender inequality at the senior management level within the professional associations that govern the property profession. The professional associations are uniquely placed to show leadership in promoting gender equality and should be adopting policy within the organisations charter to being about a shift in attitudes to women within management roles in the property industry. Social implications: – The issue of gender equity is highly topical and this paper adds to the research in this area. It highlights the important role that professional associations could take in bringing about change, but reveals that many professional bodies have a worse gender balance at the governance level than many of their member firms. Originality/value: – The paper is the first to analyse the gender mix within the professional bodies in Australia which govern and advise the property and construction industries. As such it reveals that little progress has been made in bringing about gender equality in the profession.